MIS Problems and Failures: A Socio-Technical Perspective - Bostrom, Robert P.; Heinen, J. Stephen (MIS Quarterly, 1977)
This article provides, by means of a hypothetical example, the procedures to be followed in applying the Socio-Technical-Systems Approach to information systems design. The need for this approach was presented in the first part of this article which appeared in the September Issue of the MIS Quarterly. Here the authors provide an overview of the Socio-Technical-Systems procedure and show how it could be used in redesigning an information system used by the circulation department of a large newspaper. The step by step approach is intended to illustrate the process to those practitioners feeling that more needs to be done in the area of using computer-based systems to improve the quality of working life of the system users.